2021
DOI: 10.1186/s12967-021-02718-4
|View full text |Cite
|
Sign up to set email alerts
|

Second trimester maternal serum D-dimer combined with alpha-fetoprotein and free β-subunit of human chorionic gonadotropin predict hypertensive disorders of pregnancy: a systematic review and retrospective case–control study

Abstract: Background This study investigated whether maternal serum D-dimer (DD) alone or DD combined with alpha-fetoprotein (AFP) and free β-subunit of human chorionic gonadotropin (free β-hCG) in the second trimester could be used to predict hypertensive disorders of pregnancy (HDP). Materials and methods In this retrospective case–control study, the data of gravidas patients who delivered at hospital were divided into the following groups: control (n = 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
1
1
Order By: Relevance
“…Our research also showed that the AUCs of DD in the first trimester for GH, PE, and SPE were 0.699, 0.784 and 0.893, respectively; these values were greater than the results we obtained previously in later pregnancy (the AUCs of DD for GH, PE, and SPE were 0.560, 0.614, and 0.640, respectively) [ 26 ], but was slightly lower than the results in the second trimester (the AUCs of DD for GH, PE, and SPE were 0.642, 0.767, and 0.905, respectively) [ 27 ]. These findings indicated that the levels of DD in the first trimester had a higher diagnostic value than in the middle and late trimesters for GH and PE.…”
Section: Discussioncontrasting
confidence: 66%
“…Our research also showed that the AUCs of DD in the first trimester for GH, PE, and SPE were 0.699, 0.784 and 0.893, respectively; these values were greater than the results we obtained previously in later pregnancy (the AUCs of DD for GH, PE, and SPE were 0.560, 0.614, and 0.640, respectively) [ 26 ], but was slightly lower than the results in the second trimester (the AUCs of DD for GH, PE, and SPE were 0.642, 0.767, and 0.905, respectively) [ 27 ]. These findings indicated that the levels of DD in the first trimester had a higher diagnostic value than in the middle and late trimesters for GH and PE.…”
Section: Discussioncontrasting
confidence: 66%
“…D-dimer is one of the most valuable biomarkers to exclude venous thromboembolism disorders in pregnant women and non-pregnant population ( 10 , 11 ). Previous studies have shown that D-dimer levels might predict a higher risk of pregnancy failure in women who underwent in-vitro fertilization and guide anticoagulant treatment in recurrent pregnancy loss associated with antiphospholipid syndrome; the high levels of D-dimer detected at more than 20 weeks of gestation were related to the severity of preeclampsia and maternal serum D-dimer combined with alpha-fetoprotein (AFP) and free β-subunit of human chorionic gonadotropin (free β-hCG) at the second trimester of pregnancy might be used to predict hypertensive disorders of pregnancy ( 12 15 ). However, there has been little research on the associations of maternal D-dimer level with fetal birthweight.…”
Section: Introductionmentioning
confidence: 99%